Translation and Transcultural Adaptation of the Universal Design for Learning Observation Measurement Tool (UDL-OMT) - Daniela Gäng-Pacifico; Laura Rusconi (Education Sciences)
Universal Design for Learning (UDL) is a widely accepted educational approach in the United States, and its adoption is increasingly observed in Europe and other international contexts. This growing implementation necessitates the development of standardized criteria for consistent evaluation of UDL in educational settings. This study describes the methodology for translating and cross-culturally adapting the UDL Observation and Measurement Tool (UDL-OMT), originally developed by Basham et al., into French and Italian. It also reports the results of a pretest conducted to evaluate the adapted instruments. Preliminary results indicate a high degree of adaptability of UDL-OMT for use in the French- and Italian-speaking regions of Switzerland. These results are discussed in the context of the potential for wider dissemination and validation of the instrument in French- and Italian-speaking classrooms.